Collision Tumor in the Pituitary, Concurrent Pituitary Adenoma, and Craniopharyngioma. (8th September 2020) - Shareef, Zaid; Kerndt, Connor; Nessel, Trevor; Mistry, Devin; Figueroa, Bryan
Abstract : Collision tumors are two independent, distinct tumors occupying the same anatomical space. This case presents a pituitary adenoma-craniopharyngioma collision tumor presenting with hemianopsia. A 60-year-old with a past history of a nonsecretory pituitary adenoma presented with progressive headaches, bitemporal hemianopsia, and nausea. Previously, in 2008, his adenoma was effectively treated with nasal septal flap and transsphenoidal pituitary resection. A magnetic resonance imaging (MRI) was ordered for concern of recurrence, given his history and neurologic complaints. The MRI revealed a suprasellar mass extending into the third ventricle with displacement of the hypothalamus and optic chiasm. Laboratory testing revealed no indicators of endocrinopathy. The neurosurgical and otolaryngologic teams were elected to perform tumor resection given the ongoing symptoms. An image-guided transsphenoidal tumor resection with abdominal fat graft harvest and septal mucosal flap CSF leak repair was performed. Histopathological examination revealed two tumor components within the resection including an adamantinomatous craniopharyngioma and recurrent pituitary adenoma.